2017
DOI: 10.1007/7854_2017_15
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Animal Models for Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a group of complex neurodevelopmental conditions characterized by deficits in social communication and by repetitive and stereotypic patterns of behaviors, with no pharmacological treatments available to treat these core symptoms. Oxytocin is a neuropeptide that powerfully regulates mammalian social behavior and has been shown to exert pro-social effects when administered intranasally to healthy human subjects. In the last decade, there has been a significant interest in using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 116 publications
0
29
0
Order By: Relevance
“…Oxytocin (OT) and its signaling pathway, the OT-system, are disrupted in several animal models of neurodevelopmental disorders characterized with autism-like phenotypes (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin (OT) and its signaling pathway, the OT-system, are disrupted in several animal models of neurodevelopmental disorders characterized with autism-like phenotypes (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, knock-out mouse models of Ot (3,4), oxytocin receptor (Oxtr) (5-7), or ADP-ribosyl cyclase (Cd38) (8,9) genes show changes in social behavior. In addition, several rodent models of autism spectrum disorders (ASD) endophenotypes due either to the inactivation of genes such as Fmr1, Cntnap2, Magel2, Oprm1, or to environmental valproic acid exposure (VPA), exhibit a disruption of the brain OT-system (1). Many of these models have in common at least two constant phenotypes (10).…”
Section: Introductionmentioning
confidence: 99%
“…The last two decades have been enriched with studies exploring the behavioral effects of the pro-social oxytocin (OXT) neuropeptide (Heinrichs et al, 2003 , 2009 ; Kirsch et al, 2005 ; Guastella et al, 2008a , b ; Marsh et al, 2010 ; Guastella and MacLeod, 2012 ) and its mechanisms of action (Blume et al, 2008 ; Jurek et al, 2012 ; van den Burg et al, 2015 ). In parallel, several clinical and preclinical studies have focused on the therapeutic potential of OXT, mainly to treat social behavior deficits (Guastella and Hickie, 2016 ; Wagner and Harony-Nicolas, 2017 ). However, little attention has been paid to the possible implication of the OXT system in neurodevelopmental disorders and to whether perturbation in OXT may contribute to the social behavior phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results suggest that OXT and arginine vasopressin (AVP) may play a role in the etiopathogenesis of ASD [20]. The effects of oxytocin on social cognition and behavior have recently attracted considerable attention and numerous papers have researched the possible role of oxytocin as therapeutic agent to treat ASD [21,22]. Animal models also demonstrated that the neuropeptide oxytocin plays an important role in social recognition and bonding.…”
Section: Discussionmentioning
confidence: 99%